2017
DOI: 10.7863/ultra.16.06059
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Widely Available Video Instructional Materials for Point-of-Care Ultrasound-Guided Procedure Training in Internal Medicine

Abstract: The 27 videos reviewed contained good-quality general instruction. However, we noted a lack of safety-related information in most of the available videos. Further development of resources is required to teach internal medicine trainees skills that focus on the safety of point-of-care US guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Among the remaining 18 studies, from which an average percentage of total possible QRT score could be computed or extracted, the average score was 44% with a range of 9%-71% (Figure 1). [10][11][12]14,[22][23][24]29,34,36,37,[39][40][41][42]44,47,48 The lowest mean score among studies that used internally validated QRTs was reported by Erdem and Karaca (10%), which used broad search criteria and videos from multiple author types. 23 Ferhatoglu et al, which also reported a low mean QRT score (13%), used a comprehensive QRT in which the authors analyzed each step of sleeve gastrectomy surgery.…”
Section: Video Content Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Among the remaining 18 studies, from which an average percentage of total possible QRT score could be computed or extracted, the average score was 44% with a range of 9%-71% (Figure 1). [10][11][12]14,[22][23][24]29,34,36,37,[39][40][41][42]44,47,48 The lowest mean score among studies that used internally validated QRTs was reported by Erdem and Karaca (10%), which used broad search criteria and videos from multiple author types. 23 Ferhatoglu et al, which also reported a low mean QRT score (13%), used a comprehensive QRT in which the authors analyzed each step of sleeve gastrectomy surgery.…”
Section: Video Content Qualitymentioning
confidence: 99%
“…Seven studies reported on the relationship between the video author type and scores on various QRTs (Figure 2). [22][23][24]36,39,40,42 Videos with authors classified as academic-physicians had higher internally validated QRT mean scores (46%) than those with authors classified as nonacademic-physicians or other (26%; P < .05, 95% confidence interval: 0.74-40.00). However, videos with authors classified as academic-physicians also had a wide range in QRT scores (range: 25%-75%).…”
Section: Relationship Of Video Author Type To Quality Ratingmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the lack of ultrasound‐trained faculty in medical education is a nationwide problem and is listed among the top potential barriers to integration within educational curricula . Most of the educational opportunities for internists have consisted of open‐access online educational videos and industry‐sponsored programs …”
Section: Training In Point‐of‐care Ultrasonographymentioning
confidence: 99%
“…26,[43][44][45] Most of the educational opportunities for internists have consisted of open-access online educational videos and industry-sponsored programs. 46,47 Some training, particularly for critical care physicians, is offered by organizations such as the World Interactive Network Focused on Critical Ultrasound, and the American College of Chest Physicians now offers a Certificate of Completion program in Critical Care Ultrasonography. 48,49 Additionally, the Society of Hospital Medicine, in conjunction with the American College of Chest Physicians offers an "Essentials in Critical Care" course and Certificate of Completion in POCUS.…”
Section: Expansion Of Point-of-care Ultrasonography To the Primary Ca...mentioning
confidence: 99%